Leveraging AI for Inclusive Climate Services in Kenya (and Beyond) - Grossi, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Women need tailored advisories to support their adaptation and without inclusive design, digital climate services can unintentionally reinforce harmful inequalities. This presentation explores how we can harness the power of AI to create more gender-responsive and gender-sensitive advisory services for farmers.